Primary School Pupils’ Attitude Towards Violence in the TV Serial: Arka Sokaklar - Gedik, Ezgi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: The study seeks to explore violence in Arka Sokaklar (Back Streets) serial on children. The aforementioned serial is a detective serial and is very popular both in Turkey and Turkish Republic of Northern Cyprus. It is on the air in a national channel in Turkey. Old episodes are during the weekdays; yet new episodes are on Saturday nights. Arka Sokaklar serial started to be broadcasted in 2006 and managed to be still on up to today. It is a detective serial that presents a different part of every life. In the detective serials there is certain amount of elements of violence present. Despite other studies that investigate the influence of televison on children, the present study seeks to explore attitudes of primary school pupils towards violence they are exposed on television. The study is a quantitative study. Inhouse questionnaire is prepared and applied in the state primary schools that are in Famagusta region. SPSS 18 programme has been used in the analysis of data. Reliability of the questionnaire is found 0.9774. According to the survey results, it has been found out that primary school pupils watch the television at least 1-2 hours a day. Also statistically significant relationship has been observed between the amount of time pupils spend on watching television and success in their courses. The results of the study indicate that children have difficulty in differentiating between fact and fiction. Keywords: Children, television, serials, violence, detective story, learning from television. ………………………………………………………………………………………………………………………… ÖZ: Bu çalışma Arka Sokaklar dizisindeki şiddetin çocuklar üzerindeki etkisini ortaya koymaktadır.Söz konusu dizi polisiye dizisi olup Türkiye ve Kuzey Kıbrıs Türk Cumhuriyeti’nde çok popülerdir.Türkiye’de yayın yapan ulusal bir kanalda yayınlanmaktadır.Eski bölümleri haftaiçi yayınlanmakta; yeni bölümleri ise Cumartesi geceleri yayınlanmaktadır. Arka Sokaklar dizisi 2006 yılında yayın hayatına başlamış ve günümüze kadar yayında kalmayı başarmıştır. Her bölümünde günlük hayattan ayrı bir kesiti sunan polisiye dizisidir. Polisiye dizilerde belli ölçülerde şiddet öğeleri bulunmaktadır. Televizyonun çocuklar üzerindeki etkisini araştıran diğer çalışmaların aksine bu araştırma ilkokul çocuklarının televizyonda izlediği şiddete karşı olan tutumlarını incelemeyi amaçlamıştır.Bu çalışma nicel araştırmadır. Hazırlanan anket yaşları 9 ile 11 arasında değişen Gazimağusa’da yeralan devlet ilkokullarında uygulanmıştır. Araştırmada verilerin çözümlenmesinde SPSS 18 istatistik programı (SPSS) kullanılmıştır. Anketin güvenirliği 0,9774 olarak bulunmuştur.Araştırma sonuçlarına göre ilkokul öğrencilerinin gün içerisinde en az 1-2 saat televizyon izlediği tespit edilmiş. Aynı zamandaçocukların televizyon izleme süreleri ile ders başarıları arasında anlamlı bir sonuç elde edilmiştir. Çalışmanın sonuçları çocukların gerçek ile kurguyu ayırt etmekte zorlandıklarına işaret etmektedir. Anahtar kelimeler:Çocuk, televizyon, diziler, şiddet, polisiye dizi, televizyondan öğrenme.
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2014. Supervisor: Assoc. Prof. Dr. Bahire Efe Özad.
Keywords: Communication and Media Studies; Television and children - Turkey; Mass media and children; Violence in TV Films and Serials - Children and violence; Violence on television; Television Film, Serial (Arka Sokaklar); Children, Television, Serials, Violence, Detective Story, Learning From Television